Microstructure Characteristics and Corrosion Behaviors of Mg-2Zn-2Er-0.3Zr-0.3Mn Alloy under Various Rolling Reductions - Yaqi Zheng; Yuan Zhang; Yun Liu; Yaqiang Tian; Xiaoping Zheng; Liansheng Chen (Metals, 2022)
The poor corrosion resistance of magnesium alloys is one of the major obstacles to their widespread applications in the engineering field and the medical field. A hot deformation process is the main way to improve the corrosion resistance of magnesium alloys. In the present study, X-ray photoelectron spectroscopy (XPS), a scanning electron microscope (SEM), an electron probe micro-analyzer (EPMA) and X-ray diffraction (XRD) were used to investigate the micro-galvanic corrosion behavior and film protection mechanism of hot-rolled Mg-2Zn-2Er-0.3Zr-0.3Mn under 25%, 50% and 75% thickness reductions in Hank’s solution. The results revealed that the best corrosion resistance was obtained in the alloy under a 75% thickness reduction, with a corrosion rate of 0.85 mm/y. The improvement in anti-corrosion was due to the coupling effect of a refined microstructure and dense degradation film on the large deformation hot-rolled alloy. Furthermore, the elements Mn and Er participated in the film formation and stabilized the film structure.